The Potential Role of Oxidative Stress in Modulating Airway Defensive Reflexes - Yuki Sato; Yoichiro Sugiyama; Tomoya Ishida; Haruhiko Inufusa; Fukka You; Davis Joseph; Shigeru Hirano (Antioxidants)
Airway defensive reflexes, such as pharyngeal swallowing, coughing, and sneezing, play a pivotal role in maintaining airway homeostasis. These reflexes are controlled by complex mechanisms primarily governed by specific neuronal circuitry in the brainstem, referred to as central pattern generators. These behaviors also require optimal conditions for the peripheral organs within the airway and alimentary tracts, including the nose, pharynx, larynx, and trachea, which are vital for ensuring appropriate responsiveness and motor outputs. Oxidative stress is linked to the development and progress of impaired functions of those behaviors. Dysphagia caused by central or peripheral impairments, such as neurodegeneration of related neuronal networks and laryngeal desensitization, is likely associated with an increased level of oxidative stress. Chronic inflammation and allergic airway sensitization in the lower airways, including asthma, elevate oxidative stress levels and diminish the activity of antioxidant defense enzymes, which exacerbate the severity of respiratory conditions. Antioxidant supplements offer promising therapeutic benefits by facilitating the recovery of distorted airway defensive reflexes, although limited information has been provided concerning therapeutic strategies. Further studies are necessary to enhance our understanding of the pathophysiology of dysphagia and airway diseases related to oxidative stress, as well as to develop new treatment strategies for these disorders.